The Influence Cognitive Behavioral Therapy To Resilience in Adolescents at Risk - Ayu, Nyimas Natasha; Saputra, Nofrans Eka (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2015)
ABSTRACT Introduction : Adolescents at risk is a high-risk group involved in the problems associated with behavioral health problems such as smoking, drug abuse, drinking, bullying and sexual behavior. Cognitive behavioral therapy as an active therapy is one of the alternative ways to improve resilience in adolescents at risk. Method : This study aims to find a deskriptions of risk behavior in adolescents and to determine the difference resiliency capabilities at risk pre and post the cognitive behavioral therapy. Collecting data is using risk behavior questionaire and resilience scale. Population with characteristic 13 – 19 years old adolescents at risk.. Samples were taken by using purposive random sampling technique. Experimental design of this study is true experimental pretest-postest control group design. Paired sample T test is used to analize the data. Result : This study shows that adolescents at risk have been doing bullying, smoking, drug abuse, and active sexual behavior. This study also shows that there is a significant difference of resilience ability pre and post the cognitive behavioral therapy for the experimental group, with p=0,009. While the control group showed no differences in adolescent resilience ability pre or post cognitive behavioral therapy with p=0,976 Conclusions And Recommendations : Adolescents who have risky behaviors can improve their resiliensy by using cognitive behavioral therapy. School is expected to be able to cooperate with stakeholders in preparing sustainable activities to reduce the risk behaviour in adolescents. Keywords: Adolescents at risk, resiliency, cognitive behavioral therapy.